Inovasi Pengolahan Ketela Pohon sebagai Alternatif Pendapatan Tambahan Keluarga di Kelurahan Podorejo Kecamatan Ngaliyan Kota Semarang - Teti Susilowati; Emy Susiatin; Mieftakhul Fuady; Wahyu Puspitasari (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
Podorejo Village is located in the westernmost part of Ngaliyan District, Semarang City, bordering Kendal Regency. Its area is quite large compared to other villages in the district. Its population is around 10,000. Most of them make their living from farming, while others engage in trade. The area consists of agricultural land and gardens, most of which are planted with cassava. Cassava is a prominent commodity in the region, but its utilization has not been optimally optimized.Seeing the potential of the region, the Community Service team conducted entrepreneurship outreach to housewives in the area, utilizing local commodities, namely cassava, as the basic ingredient for various processed foods as an alternative business to help supplement family income. This outreach will increase the economic value of cassava, which previously only processed into chips and cassava tape. By innovating cassava processing into contemporary foods that are popular with children and ready to be sold in the market.Our community service activities included outreach on entrepreneurship, motivating women to start businesses utilizing cassava through various innovations. The activity took place on October 19, 2025, with 18 participants. They were very enthusiastic about participating. The outreach program resulted in an increased understanding of entrepreneurship and its management, skills, and interest in starting a business. Evaluation results showed an increase in understanding, exceeding 50%, after pre- and post-tests. The target output of this community service program is publication in national journals, HKI videos, YouTube, and through mass media.